The effectiveness of a protection law in favor of conservation of an marine resource: The example of the ghost shrimp Callichirus major (Decapoda, Callianassidae) of the coast of Brazil - Hernáez, Patricio [UNESP]; Hereman, Michael J. [UNESP]; Pimenta, Camila E. R. [UNESP]; Rio, Juliana P. P. [UNESP]; João, Marcio C. A. [UNESP]; Pinheiro, Marcelo A. A. [UNESP] (FapUNIFESP (SciELO), 2019)
Studies on mortality due to fishing based on isolating the effect caused by catches are scarce. The present study analyzed this aspect using the ghost shrimp Callichirus major (Say, 1818) as a biological model, which is heavily harvested along the Brazilian coast. For that purpose, density of burrows and population structure of C. major was examined at two adjacent beaches, Gonzaga and Itararé, from the State of São Paulo, Brazil. Gonzaga beach was considered as control because since 1992 a municipal law prevents the capture of C. major, whereas Itararé as treatment since in this place the species is harvested throughout the year. Burrow density and female CL size were significantly higher in Gonzaga than that Itararé. Sex-ratio did not differ significantly from 1:1 in Itararé, differing from the observed in the area without fishing mortality and also to the general pattern reported in other species of ghost shrimps in which females outnumbered than males. Reproductive potential was significantly smaller in Itararé than Gonzaga, as result of the reduced number of females present in this area relative to Gonzaga. A preliminary estimation indicates that 71% of shrimps in Itararé died as result of fishing. This information suggests non-viability of C. major in this area given the current pressure of fishing. Presence of C. major in the beach of Itararé and probably in other nearby areas where exploitation occurs would be favored by the permanent supply of larvae from Gonzaga beach where the species is protected by and municipal surveillance.
La efectividad de una ley de protección al servicio de la conservación de un recurso marino: El ejemplo del camarón fantasma Callichirus major (Decapoda, Callianassidae) de la costa de Brasil
Keywords: Artisanal fishery; Mortality; Population structure; Reproduction; South western atlantic